2012
DOI: 10.1016/j.jana.2011.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Quality of Life Among People Living With HIV (PLWH) in Suphanburi Province, Thailand

Abstract: This study examined the relationships between personal characteristics, social support, spiritual well-being, coping style and adaptation process, and quality of life (QOL) among Thai people living with HIV infection (Thai PLWH) in Suphanburi Province, Thailand. Predictors of QOL were also investigated. Molassiotis's Quality of Life Assessment in Chronic Patients provided the theoretical framework for this descriptive correlational design. The sample consisted of 120 Thai PLWH. Multiple regressions were used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
0
8

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 22 publications
3
18
0
8
Order By: Relevance
“…Similar to the previous studies [12–14], participants with higher education levels (BS or higher) reported better QoL in physical, social, and environmental domains. The contribution of education is particularly prominent in the environmental domain.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Similar to the previous studies [12–14], participants with higher education levels (BS or higher) reported better QoL in physical, social, and environmental domains. The contribution of education is particularly prominent in the environmental domain.…”
Section: Discussionsupporting
confidence: 83%
“…Compared with noninfected individuals, PLWHA in all disease stages demonstrated a poor QoL in all aspects, especially in psychological and social aspects [3–5]. In literature, the poorer QoL of PLWHA was associated with the more severe disease condition, lower CD4 + T cells count, longer treatment time, poor mental health, no family support, being older, being female, and lower educational and economic levels, although it varied in degree by individual cultural contexts and available medical care in different countries [6–14].…”
Section: Introductionmentioning
confidence: 99%
“…This indicates the need for improved hepatitis management for PLHIV on ART. Patients who have higher education levels will achieve better QOL [10], possibly as they are more integrated in society and may have a better social network of family and friends. It is difficult to explain why those who witnessed the death of a family member due to HIV had better QOL improvement.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas it is well documented that ART improves not only clinical outcomes but also QOL within the first year [4,5], conclusions on what other factors (besides the ART itself) can contribute to a higher QOL are diverse [6,7]. Several factors have been identified as contributing to better QOL among PLHIV, including social support [8,9], spiritual well-being [9], education level [10,11], not being an injecting drug user [12,13] and having good adherence to ART [14,15]. Meanwhile, other factors such as HIV-related stigma [16-18], non-disclosure of one’s HIV status have been reported to negatively affect QOL [19].…”
Section: Introductionmentioning
confidence: 99%
“…Increasing social support increases the quality of life of HIV/AIDS persons [12]. Social support is significant predictor of quality of life [13]. It is significantly associated with better quality of life, minimizes the depressive symptoms among HIV/AIDS patients [14].…”
Section: Introductionmentioning
confidence: 99%